THE RESPONSIBILITY OF NOTARIES AS PUBLIC SERVANTS REGARDING DESIRED AGREEMENT DEEDS USING BRAILLE SCRIPT - Retno Wahyu Nickent Cassy; Muktiono; Erna Anggraini (RADJA PUBLIKA, 2023)
This research examines the aspects of the notary's responsibility as a public servant, specifically regarding individuals with disabilities, in relation to Law Number 25 of 2009 on Public Services. The notary is involved and has the responsibility to provide services to the public. In this study, the researcher addresses two topics: the duties and responsibilities of the notary as a public servant, and the use of Braille script in desired deeds. To answer these two discussions, the author adopts a normative juridical approach through the study of legal materials and literature sources related to the chosen theme. The research findings indicate that the notary has a workload of tasks and responsibilities as a public servant in the private realm, and copies as well as minutes of deeds can be made using Braille script. The International Organization's Notarial Guide of Good Practices for People With Disabilities has recommended the establishment of specific regulations for individuals with disabilities, essentially allowing the use of Braille script in deeds as a way to maximize services.